2002
DOI: 10.1021/jm025540g
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Novel Taxoid−Monoclonal Antibody Conjugates

Abstract: Taxoids bearing methyldisulfanyl(alkanoyl) groups for taxoid-antibody immunoconjugates were designed, synthesized and their activities evaluated. A highly cytotoxic C-10 methyldisulfanylpropanoyl taxoid was conjugated to monoclonal antibodies recognizing the epidermal growth factor receptor (EGFR) expressed in human squamous cancers. These conjugates were shown to possess remarkable target-specific antitumor activity in vivo against EGFR-expressing A431 tumor xenografts in severe combined immune deficiency mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 19 publications
3
120
0
4
Order By: Relevance
“…31 However, the nondiscriminating side effects on normal tissue and the multi drug resistance limited the efficacy of Taxol. 14,32 The EC 50 of A431 cells to Taxol alone is about 90 pM, 32 our data showed that the IC 50 of the Fab-Taxol conjugate was about 20 pM (Fig. 6A), four-to five-fold more potent than Taxol when analyzed by the cell proliferation inhibition assay.…”
Section: Discussionmentioning
confidence: 68%
“…31 However, the nondiscriminating side effects on normal tissue and the multi drug resistance limited the efficacy of Taxol. 14,32 The EC 50 of A431 cells to Taxol alone is about 90 pM, 32 our data showed that the IC 50 of the Fab-Taxol conjugate was about 20 pM (Fig. 6A), four-to five-fold more potent than Taxol when analyzed by the cell proliferation inhibition assay.…”
Section: Discussionmentioning
confidence: 68%
“…Antibodies (their size is about 12 nm) endowed with fluorescent dyes (e.g., Alexa Fluor 488 λEm=525 nm and Texas Red λEm=609 nm) [15][16][17] were used in the development of a wide range of effective targeted therapies [18][19][20][21][22] but they create clustering artifacts due to limited antibody penetration, which have an impact on insufficient labeling density. Thus, ligands that have been exploited for chemotherapeutic agent targeting systems can include monoclonal antibodies [23][24][25][26][27][28] but also low molecular weight receptor-binding conjugates such as dyelabeled peptides (arginine-glycine-aspartic acid-Cyt5,5) [29], peptide hormones [30,31], receptor antagonist and agonists [32], aptamers [33][34][35], transferrin [36][37], oligosaccharides [38], glycoconiugates [39], polyunsaturated fatty acids [40], oligopeptides [41,42], vitamin B12 [43], folic acid [44][45][46][47][48][49][50][51][52][53][54] and hyaluronic acid [55,56]. These ligands can be regarded as a tumor-specific receptor to construct a "guided molecular ...…”
Section: Fluorescent Small Molecules As Cell-type-specific Imaging Prmentioning
confidence: 99%
“…It is also a stabiliser of microtubules and is cytotoxic against several human cells. It is used in the treatment of locally advanced metastatic breast cancer and non-small-cell lung cancer [152][153][154][155][156] (Fig. 9).…”
Section: Paclitaxel (Taxol ® ) and Docetaxel (Taxotere ® )mentioning
confidence: 99%